Current treatments for renal failure due to multiple myeloma - Gavriatopoulou, M.; Terpos, E.; Kastritis, E.; Dimopoulos, M.A. (Expert Opinion on Pharmacotherapy, 2016)
Introduction: Renal impairment (RI) is one of the most common complication of multiple myeloma (MM). RI is present in almost 20% of MM patients at diagnosis and in 40%-50% of patients during the course of their disease. Areas covered: Biology along with tools for diagnosis and management of RI are reported in this paper. Papers published in PubMed and reported abstracts up to May 2016 were used. Expert opinion: Moderate and severe RI increases the risk of early death; thus rapid intervention and initiation of anti-myeloma treatment is essential and improves renal outcomes in RI patients. Bortezomib and dexamethasone triplet combinations are the current standard of therapy for MM patients with acute kidney injury due to cast nephropathy; they offer high rates of both anti-myeloma response and renal recovery. Thalidomide and lenalidomide may be used in bortezomib refractory patients. In the relapsed/refractory setting additional treatment options such as carfilzomib, pomalidomide and monoclonal antibodies are available; however, there is limited data for their effects on patients with RI. High dose melphalan with autologous stem cell transplantation should be considered in otherwise eligible patients with RI. Finally, high cut-off hemodialysis membranes do not seem to offer significant additive effects on anti-myeloma therapies. © 2016 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: autologous stem cell transplantation (ASCT); bortezomib; cast nephropathy; high-cut off hemodialysis; immunomodulatory drugs (IMiDs); multiple myeloma; novel agents; renal impairment